Comparison of 1 and 2 weeks of omeprazole, amoxicillin and clarithromycin treatment for Helicobacter pylori eradication: the HYPER Study. Issue 4 (6th October 2006) - Zagari, Rocco Maurizio; Bianchi-Porro, Gabriele; Fiocca, Roberto; Gasbarrini, Giovanni; Roda, Enrico; Bazzoli, Franco
Abstract : Background: Triple therapy is recommended for Helicobacter pylori eradication, yet consensus on the duration of treatment is lacking. Aim: To compare the efficacy and safety of 1- and 2-week regimens of omeprazole, amoxicillin and clarithromycin in a large, multicentre, double-blind and randomised study. Methods: A total of 909 H pylori -positive patients with duodenal ulcer, enrolled in 81 endoscopy units in Italy, were randomised to receive omeprazole, amoxicillin and clarithromycin for either 1 week (OAC1W) or 2 weeks (OAC2W) or omeprazole and amoxicillin for 2 weeks. H pylori eradication was assessed by histological examination and carbon-13 urea breath test 4 weeks after treatment. Results: Both the intention-to-treat (ITT; n = 907) and per protocol (PP; n = 661) analyses showed no significant differences between the eradication rates of OAC1W (ITT 79.7%; PP 83.6%) and OAC2W (ITT 81.7%; PP 84.9%; ITT p = 0.53; PP p = 0.71). Both triple omeprazole, amoxicillin and clarithromycin regimens gave significantly higher eradication rates compared with omeprazole and amoxicillin treatment (ITT 44.6%; PP 42.8%; p<0.001). Poor compliance was reported in 18.6%, 17.3% and 15.1% (p = 0.51) of patients for OAC2W, OAC1W and omeprazole and amoxicillin, respectively. Adverse events occurred in 9.9% and 9.6% (p = 0.88) of patients for OAC2W and OAC1W, respectively, and in 5.9% for omeprazole and amoxicillin (p = 0.11). Conclusions: 1-week and 2-week triple treatments for H pylori eradication are similar in terms of efficacy, safety and patient compliance.